Impact of Thermal-Induced Turbulent Distribution Along FSO Link on Transmission of Photonically Generated mmW Signals in the Frequency Range 26–40 GHz - Luis Vallejo; Matej Komanec; Beatriz Ortega; Jan Bohata; Dong-Nhat Nguyen; Stanislav Zvanovec; Vicenc Almenar (IEEE Photonics Journal, 2020)
Microwave photonics is a promising solution to transmit millimeter wave (mmW) signals for the 5th generation (5G) mobile communications as part of a centralized radio access network (C-RAN). In this paper, we experimentally evaluate the impact of turbulent free space optics links on photonically generated mmW signals in the frequency range of $\text{26}-\text{40}\text{ GHz}$ . We analyze the remote generation of mmW signals over hybrid links based on free-space optics (FSO) and standard single mode optical fiber (SSMF) with $ - \text{39.97}\;\text{dBm}$ received electrical power and phase noise level at $\text{100}\;\text{kHz}$ as low as $ - \text{95.92}\;\text{dBc}\;\text{Hz}$ at $\text{26}\;\text{GHz}$ . Different thermal distributions along the FSO link have been implemented and Gamma-Gamma model has been employed to estimate the thermally induced turbulence. The results show high electrical power decrease and fluctuation of the generated mmW signal according to the particular level of the turbulence in terms of refractive index structure parameter and thermal distribution along the FSO link. $\text{8}\;\text{Gb}/\text{s}$ 16-quadrature amplitude modulation (QAM) data transmission at $\text{42}\;\text{GHz}$ has been demonstrated over the hybrid link with minimal error vector magnitude (EVM) value of $\text{5}{\%}$ whereas turbulent FSO link introduced up to $\text{5}\;\text{dB}$ power penalty.